Risco de interações medicamentosas em pacientes com câncer e recebendo cuidados de suporte exclusivo - Riechelmann, Rachel Simões Pimenta [UNIFESP] (2009)
Background: Drug-drug interactions (DDIs) comprise an important problem in medical oncology practice. We systematically reviewed the frequency of DDIs in oncology. Methods: We searched PubMed for eligible articles and online databases abstracts of major oncology meetings. Results: Eight studies reported on the frequency of DDIs: six evaluated the frequency of potential DDIs while 2 studies reported on real DDIs, i.e. interactions that had clinical consequences. Studies of potential DDIs found that approximately one third of patients are exposed to dangerous drug doublets, with the most common ones involving warfarin and anticonvulsants. One study of real DDIs found that 2% of hospitalized cancer patients had a DDI as the cause of admission. Conclusion: Drug interactions comprise an important issue in oncology, with approximately one third of ambulatory cancer patients being at risk of DDIs. Data are limited on the clinical consequences of drug interactions among cancer patients.